Emerging trends in epigenetic and childhood trauma: Bibliometrics and visual analysis - Nie, Yuting; Wen, Lulu; Song, Juexian; Wang, Ningqun; Huang, Liyuan; Gao, Li; Qu, Miao (Frontiers in Psychiatry, 2022)
Background: The epigenetic study of childhood trauma has become a valuable field. However, the evolution and emerging trends in epigenetics and childhood trauma have not been studied by bibliometric methods. Objective: This study aims to evaluate status of epigenetic studies in childhood trauma and reveal the research trends based on bibliometrics. Methods: A total of 1,151 publications related to childhood trauma and epigenetics published between 2000 and 2021 were retrieved from the Web of Science Core Collection (WoSCC). CiteSpace (5.8. R 3) was used to implement bibliometric analysis and visualization. Results: Since 2010, the number of related publications has expanded quickly. The United States and McGill University are the most influential countries and research institutes respectively. Elisabeth Binder is a leading researcher in childhood trauma and epigenetic-related research. Biological Psychiatry is probably the most popular journal. In addition, comprehensive keyword analysis revealed that "glucocorticoid receptor", "brain development", "epigenetic regulation", "depression", "posttraumatic stress disorder", "maternal care", "histone acetylation", "telomere length", "microRNA ", and "anxiety" reflect the latest research trends in the field. A comprehensive reference analysis demonstrated NR3C1 gene methylation, FKBP5 DNA methylation, BDNF DNA methylation, and KITLG methylation have been hot spots in epigenetic studies in the field of childhood trauma in recent years. Notably, the relationship between childhood adversity and NR3C1 gene methylation levels remains unresolved and requires well-designed studies with control for more confounding factors. Conclusions: As the best of our knowledge, this is the first bibliometric analysis of the association between childhood trauma and epigenetics. Our analysis of the literature suggests that childhood trauma may induce depression, anxiety, and post-traumatic stress disorder through epigenetic regulation of glucocorticoid receptor expression and brain development. The hypothalamic-pituitary-adrenal axis is the key points of epigenetic research. The current researches focus on NR3C1 gene methylation, FKBP5 DNA methylation, BDNF DNA methylation, and KITLG methylation. These results provide a guiding perspective for the study of epigenetic effects of childhood trauma, and help researchers choose future research directions based on current keywords.